THE EFFECTIVENESS OF USING COOPERATIVE LEARNING MODELS TOWARD PRE-SERVICE ELEMENTARY TEACHER’S UNDERSTANDING ON SOCIAL SCIENCE EDUCATION COURSE: A COMPARISON FOR COOPERATIVE SCRIPT, ARTICULATION, AND GUIDED NOTE TAKING - Eli Hermawati; Mia Zultrianti Sari; Yani Fitriyani (The University of Kuningan, 2020)
Our initial study in the course showed that there was a lack of students’ understanding about social science. The purpose of this study was to investigated the effectiveness of using Cooperative Learning Model (Cooperative Script, Articulation, and Guided Note Taking) towards Pre-Service Elementary Teacher understanding on Social Science Course. This research was conducted in quasi-experimental research, with counterbalance research design. The subjects of this study were first year of undergraduate students of pre-service elementary school teacher education at the University of Kuningan. The data collection technique used was an instrument test which was an essay question. The data analyzed by statistical test with the t-test (independent samples t-test) at a 95% confidence level obtained tcalc ttable and probability value sig. (2-tailed) 0.05. The results of this study proved that there are differences in students' understanding so that the hypothesis is accepted. In our context, Cooperative Script was more sophisticated in improving student understanding compared to Articulation and Guided Note Taking. The limitation of our context means that there is no best method to be applied.Keywords: understanding; cooperative script; articulation; guided note taking; pre-service elementary teacher